A case of recurrent intracranial hemorrhage in CADASIL caused by NOTCH3 c.1759C>T heterozygous mutation. Issue 2 (5th January 2023) - Chu, Ying; Wang, Qi; Ma, Yue; Xu, Linying; Ren, Kexin; Liu, Jiahui; Tao, Dingbo; Cao, Hua; Ji, Xiaofei
Abstract: Background: Cerebral autosomal‐dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a cerebrovascular disease that is closely related to the NOTCH3 gene. Recurrent ischemic stroke, progressive cognitive dysfunction, and mental symptoms are the main clinical manifestations, whereas symptomatic intracranial hemorrhage is rare. Methods: We detected a heterozygous mutation of c.1759C>T in exon 11 of the NOTCH3 gene that caused recurrent intracranial hemorrhage in CADASIL. Results: Second‐generation sequencing of a sample of the patient's genome revealed a heterozygous mutation of c.1759C>T in exon 11 of NOTCH3, which resulted in amino acid changes (p.R587C). This variation may be rated as a CADASIL clinical variation. Conclusion: The discovery of this mutation site provides an important theoretical basis for a gene‐based diagnosis and treatment of recurrent intracranial hemorrhage.